Pengambilan Keputusan Pada Pernikahan Dini Di Indonesia : Studi Fenomenologi Remaja Di Indonesia - Mariana Irbach Khonsa Rahmayanti; Amalia Indah Savitri; Adam Jamal (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Early marriage is a common social phenomenon and causes the number of early marriages in Indonesia to rise from year to year. The factors that occur can influence a person's decision to marry at a young age. Decision-making is a process of choosing the alternative that the individual considers to be the best. It encompasses the stages through which the individual must go, at each stage the individual is confronted with the alternative he has to choose in achieving the desired goal. The method in this research uses descriptive qualitative research, with the approach of the type of research that is literature study or library study. The results of the study suggest that there are several factors that need to be considered in decision-making to be able to marry at a young age. In addition, internal and social factors are subject considerations that need to be taken into account in the decision-making process including a person's mental or psychological readiness, economic factors, and also social support.